Influence of institutional experience and technological advances on outcome of stereotactic body radiation therapy for oligometastatic lung disease - Hörner-Rieber, Juliane; Streblow, Jan; Uhlmann, Lorenz; Sterzing, Florian (International journal of radiation oncology, biology, physics, 2017)
Purpose: Many technological and methodical advances have made stereotactic body radiotherapy (SBRT) more accurate and more efficient during the last years. This study aims to investigate whether experience in SBRT and technological innovations also translated into improved local control (LC) and overall survival (OS). Methods and Materials: A database of 700 patients treated with SBRT for lung metastases in 20 German centers between 1997 and 2014 was used for analysis. It was the aim of this study to investigate the impact of fluorodeoxyglucose positron-emission tomography (FDG-PET) staging, biopsy confirmation, image guidance, immobilization, and dose calculation algorithm, as well as the influence of SBRT experience, on LC and OS. Results: Median follow-up time was 14.3 months (range, 0-131.9 months), with 2-year LC and OS of 81.2% (95% confidence interval [CI] 75.8%-85.7%) and 54.4% (95% CI 50.2%-59.0%), respectively. In multivariate analysis, all treatment technologies except FDG-PET staging did not significantly influence outcome. Patients who received pre-SBRT FDG-PET staging showed superior 1- and 2-year OS of 82.7% (95% CI 77.4%-88.6%) and 64.8% (95% CI 57.5%-73.3%), compared with patients without FDG-PET staging resulting in 1- and 2-year OS rates of 72.8% (95% CI 67.4%-78.8%) and 52.6% (95% CI 46.0%-60.4%), respectively (P=.012). Experience with SBRT was identified as the main prognostic factor for LC: institutions with higher SBRT experience (patients treated with SBRT within the last 2 years of the inclusion period) showed superior LC compared with less-experienced centers (P≤.001). Experience with SBRT within the last 2 years was independent from known prognostic factors for LC. Conclusion: Investigated technological and methodical advancements other than FDG-PET staging before SBRT did not significantly improve outcome in SBRT for pulmonary metastases. In contrast, LC was superior with increasing SBRT experience of the individual center.